Collective narcissism predicts hypersensitivity to in-group insult and direct and indirect retaliatory intergroup hostility - Golec, A. (2017)
Results of five studies (N = 1596) linked collective narcissism-a belief in in-group exaggerated greatness contingent on external validation-to direct and indirect, retaliatory hostility in response to situations that collective narcissists perceived as insulting to the in-group but which fell well beyond the definition of an insult. In Turkey, collective narcissists responded with schadenfreude to the European economic crisis after feeling humiliated by the Turkish wait to be admitted to the European Union (Study 1). In Portugal, they supported hostile actions towards Germans and rejoiced in the German economic crisis after perceiving Germany's position in the European Union as more important than the position of Portugal (Study 2). In Poland, they supported hostile actions towards the makers of a movie they found offensive to Poland (Studies 3 and 5) and responded with direct and indirect hostility towards a celebrity whose jokes about the Polish government they found offensive (Study 4). Comparisons with self-positivity and in-group positivity indices and predictors of intergroup hostility indicated that collective narcissism is the only systematic predictor of hypersensitivity to in-group insult followed by direct and indirect, retaliatory intergroup hostility.